2022
DOI: 10.1007/s00018-022-04300-7
|View full text |Cite
|
Sign up to set email alerts
|

Nucleolin: a cell portal for viruses, bacteria, and toxins

Abstract: The main localization of nucleolin is the nucleolus, but this protein is present in multiple subcellular sites, and it is unconventionally secreted. On the cell surface, nucleolin acts as a receptor for various viruses, some bacteria, and some toxins. Aim of this review is to discuss the characteristics that make nucleolin able to act as receptor or co-receptor of so many and different pathogens. The important features that emerge are its multivalence, and its role as a bridge between the cell surface and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 143 publications
1
20
0
Order By: Relevance
“…Mapping the causality between the antiviral effect of sncRNAs to nucleolin and RSV infection has proven to be difficult, as knocking down nucleolin significantly reduces RSV infection, which confirms that nucleolin is indeed a receptor for RSV [ 11 , 31 ]. Furthermore, as nucleolin is an essential protein involved in many cellular processes such as the proliferation, transcriptional regulation, stability and transportation of mRNA, previous studies have shown that knocking out nucleolin is lethal to cells [ 32 , 33 ], precluding the possibility of conducting such experiments to show that the functional mechanism of ssONs is blocking nucleolin. As nucleolin is the only established functional receptor for RSV to date, it would be difficult to find other interaction partners for sncRNAs in relation to RSV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Mapping the causality between the antiviral effect of sncRNAs to nucleolin and RSV infection has proven to be difficult, as knocking down nucleolin significantly reduces RSV infection, which confirms that nucleolin is indeed a receptor for RSV [ 11 , 31 ]. Furthermore, as nucleolin is an essential protein involved in many cellular processes such as the proliferation, transcriptional regulation, stability and transportation of mRNA, previous studies have shown that knocking out nucleolin is lethal to cells [ 32 , 33 ], precluding the possibility of conducting such experiments to show that the functional mechanism of ssONs is blocking nucleolin. As nucleolin is the only established functional receptor for RSV to date, it would be difficult to find other interaction partners for sncRNAs in relation to RSV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Surface expression of nucleolin has been reported in many different cancer types, and its involvement in cancer has been extensively studied (reviewed in [ 78 , 79 , 80 , 81 , 82 ]). At the cell surface, nucleolin can act as a receptor for various viruses [ 83 ]. The detailed mechanism of internalization and subcellular fate of F3-functionalized nanoparticles has been intensively studied using polyacrylamide nanocarriers (NC) and comparing targeted NC, non-targeted NC, and F3 peptide alone.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to HSPGs, two group II sPLA2s, the human one and a PLA2-like myotoxin, interact with two proteins, nucleolin (NCL) and vimentin (VIM), known for their ability to establish multiple molecular interactions both inside the cell, where they are normally found, and on the cell surface, where they are secreted by unconventional mechanisms [ 36 , 68 ]. On the cell surface, NCL and VIM interact with different membrane receptors, forming complexes that mediate the internalization of different types of viruses or other pathogens and proteins [ 71 , 72 ]. Membrane proteins with which NCL and VIM interact include integrins alpha 3, alpha 4, beta 1, and beta 3 (ITGA4, ITGA6, ITGB1, and ITGB3), the epidermal growth factor receptor (EGFR), and glypican-1 (GPC-1), all identified as group II sPLA2 receptors [ 34 ] ( Figure 3 ).…”
Section: Spla2s Are Globular Proteins But They Can Form Active Conden...mentioning
confidence: 99%